IT Convergence and Security 2017 Volume 1 - Kim, Kuinam J.; Kim, Hyuncheol; Baek, Nakhoon; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This is the first volume of proceedings including selected papers from the International Conference on IT Convergence and Security (ICITCS) 2017, presenting a snapshot of the latest issues encountered in this field. It explores how IT convergence and security issues are core to most current research, and industrial and commercial activities. It consists of contributions covering topics such as machine learning & deep learning, communication and signal processing, computer vision and applications, future network technology, artificial intelligence and robotics. ICITCS 2017 is the latest in a series of highly successful International Conferences on IT Convergence and Security, previously held in Prague, Czech Republic(2016), Kuala Lumpur, Malaysia (2015) Beijing, China (2014), Macau, China (2013), Pyeong Chang, Korea (2012), and Suwon, Korea (2011).
Keywords: Computational intelligence; Data protection; Application software; Telecommunication; Computational Intelligence; Data and Information Security; Computer and Information Systems Applications; Communications Engineering, Networks